An overview of the theme of social innovation in the three sectors: a research in the studies of the gaucho universities - Agostini, Manuela Rosing; Morás, Cássia; D'Agostini, Monalise; Carra, Laura Vitória Alves (Revista de Administração da UFSM, 2020)
Purpose – The Social Innovation (SI) theme is still considered new, however, in the last decades it has been treated with more importance, gaining prominence in the academic environment, and it has become an object of analysis in several researches. Thus, this paper aims to analyze the evolution of the SI theme in the academic scope of gaucho universities. Design/methodology/approach – The research has a theoretical-empirical nature, a qualitative and quantitative approach. It establishes a systematic review on SI, analyzes the objectives and results of a sample of 76 dissertations and theses produced in Rio Grande do Sul universities, through a systematic review of the literature with meta-analysis. Findings – After analyzing the data, we observed that the topic has become more widely addressed in recent years, however, there is still no single concept. It was identified that it is being used to address the most different issues related to innovations that modify a social relationship, being applied in the most different sectors or in an intersectoral way. Originality/value (mandatory) – The paper presents an overview of the research and a framework with the characteristics present in the SI initiatives in the five sectors, presenting suggestions for future studies. Demonstrate that the concept of SI will be increasingly used because it is an important theme in the construction of a transformation of local realities, either by generating income, by seeking improvements in the quality of life or by new ways of thinking about global sustainability.